The Political Economy of the German Länder Deficits - Beate Jochimsen; Robert Nuscheler (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
We analyze the deficits of the German Länder for the period from 1960 to 2000 and test a number of hypotheses derived from the literature on the political economy of public expenditures and public deficits. Estimating a dynamic panel data model, we find evidence for political opportunism of the Rogoff/Sibert-type. German voters seem to favor fiscal discipline as debt issue is significantly lower in pre-election years. There is no evidence for partisan behavior. Party ideology thus plays a negligible role. As suggested by the theory, coalition governments issue more debt. This effect is, however, not statistically significant. If the probability of reelection is small, the incumbent government may find it beneficial to issue more debt. We consider four different approximations of the reelection probability but find evidence for none of them.
Keywords: E60; D72; H62; 330; Public Debt; Political Economy; German Länder; Dynamic Panel Data Model; Länderhaushalt; Haushaltsdefizit; Public Choice; Deutschland